THE POTENTIAL YIELD OF THREE NEW PADDY VARIETIES AT KEBON AGUNG – BANTUL - Setyorini Widyayanti; Kristamtini Kristamtini; Sutarno Sutarno (Widyariset, 2011)
Food needs will increase every year due to population growth and changing patterns of food consumption, so it needs a good cultivation technology to increase the productivity and national food production. Some efforts have been done including the use of paddy new varieties (VUB). The purpose of this research was to investigate the yield of three new varieties of paddy rice fi eld in Imogiri, Bantul, Yogyakarta Province. The experiment was carried out in Jayan village, Kebon Agung, Imogiri, Bantul, Yogyakarta from August to November 2009. The experiment was arranged in a randomized block design with three new varieties of Inpari 1, Conde and Dodokan as treatments. Each treatment had three replicates and conducted in the total area of 3,000 m2. The results showed that Inpari 1 had the highest dry harvested grain crops (11.64 t / ha GKP), followed by Conde (11.28 t / ha GKP) and Dodokan (9.47 t / ha GKP), respectively.